1979
DOI: 10.1002/1097-0142(197907)44:1<221::aid-cncr2820440136>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis of tissue glycosaminoglycans as an aid in the diagnosis of mesotheliomas

Abstract: The histologic distinction between mesotheliomas and adenocarcinomas on mesothelial surfaces is sometimes difficult. High concentrations of hyaluronic acid in pleural and peritoneal fluids of mesothelioma patients have been reported. This paper describes results of glycosaminoglycan electrophoresis of papain digests of 7 mesotheliomas and 27 other tumors. Either all or almost all demonstrable glycosaminoglycans in mesotherliomas was hyaluronic acid. Control tissues had variable electrophoretic patterns showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is thus possible that autocrine growth stimulation involving PDGF-BB is an important step in the formation of malignant mesothelioma (Versnel et al, 1991). In addition, large amounts of hyaluronan often accumulate in mesothelioma patients (Waxler et al, 1979;Arai et al, 1979). It is thus possible that PDGF, or other factors that are produced by mesothelioma cells, stimulate the production of hyaluronan by the surrounding mesothelial cells or fibroblasts, or by the mesothelioma cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that autocrine growth stimulation involving PDGF-BB is an important step in the formation of malignant mesothelioma (Versnel et al, 1991). In addition, large amounts of hyaluronan often accumulate in mesothelioma patients (Waxler et al, 1979;Arai et al, 1979). It is thus possible that PDGF, or other factors that are produced by mesothelioma cells, stimulate the production of hyaluronan by the surrounding mesothelial cells or fibroblasts, or by the mesothelioma cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, tumor-secreted HA in the pleural fluid has been suggested as a means of identifying MPMs [31, 33, 81, 86, 90–93]. In this context, Waxler and coworkers [94] developed a method for isolating HA and other GAGs from tumor tissues and observed that MPMs contained only or almost entirely HA, whereas carcinomas and sarcomas consisted of a mixture of HA and other GAGs. Based on this, these authors concluded HA as the sole or major GAG to confirm a diagnosis of MPM.…”
Section: Diagnostic Value Of Ha In Mpmmentioning
confidence: 99%
“…An analysis of hyaluronan in these fluids has been tried as a diagnostic tool for mesothelioma, but it has not proven reliable in differentiating mesotheliomas from other malignant condition^.^^-^^"^-'^ I n order to increase the reliability of hyaluronan analyses, they have also been performed on tissue specimens from tumors, and it has been reported that high hyaluronan concentrations then show a better correlation with the diagnosis of mesothelioma. '0~'5~'7- 30 The development of new, specific assays for hyalurhas made it feasible to analyze the polysaccharide in serum. There so far has been only one short report of hyaluronan in the serum of a small number of cancer patients under treatment.32 As far as we know, no one has described hyaluronan in serum from patients with mesothelioma compared to patients with other malignant diseases.…”
mentioning
confidence: 99%